Strategi Pembelajaran Ilmu Tajwid Berbasis Matching Card di TPQ Qomaruzzaman Desa Racek Kec. Tiris - al ahdafillah, M. ahsan; Sunaidi, Sunaidi (Najah: Journal of Research and Community Service, 2025)
Teaching activities, the process of communication between students and educators is very important in order to understand the lesson. Therefore, educators must be able to deliver material using appropriate, creative, and innovative strategies so that learning takes place effectively. This study aims to determine the effectiveness of tajwid learning using the Matching Card strategy at TPQ Qomaruzzaman. The researcher observed a phenomenon occurring at TPQ Qomaruzzaman. The subjects of this study were TPQ Qomaruzzaman students who had reached Iqra 4 and Al-Qur'an levels. The results of this study show that the researcher found tajwid learning using the Matching Card strategy to be very effective because it is easier to understand, easier to memorize, concise, and involves children's activities. The supporting factors for the Matching Card strategy are enthusiasm and good communication between students and educators. Meanwhile, the inhibiting factor in the Matching strategy is the mixed ages of the students, which affects their comprehension.